A Reconsideration of Purported Holocene Bison Bones from Northern Alaska - Rasic, Jeffrey T.; Matheus, Paul E. (ARCTIC, 2009)
While bison were the most abundant large mammals in Eastern Beringia for most of the last 100 000 years, their range declined drastically at the end of the Pleistocene and through the Holocene. Research into the nature of Holocene human interactions with bison suffers from scarcity of faunal remains from most archaeological sites and poor chronological control of paleontological specimens over broad areas of Eastern Beringia. We examined the dating, context, and identification of purported bison bones spatially associated with two late prehistoric archaeological sites in northern Alaska to contribute to a better understanding of bison biogeography and the possible role of these large mammals in prehistoric economies. We confirmed the presence of two bison bones from the 17th century Kangiguksuk archaeological site (49-XBM-012) in northwestern Alaska, but radiocarbon dates older than 30 000 14C years BP for both bones demonstrate that those bison were not hunted by the site occupants. From the Lakeside site (49-KIR-275) in the central Brooks Range, a bone reported to be bison and dated to about 2400 14C years BP was shown through DNA sequencing to be moose (Alces alces). We point to a large set of dated bison specimens from Alaska’s Arctic Slope that suggests bison were locally extinct in north-central and northwestern Alaska by the beginning of the Holocene and were subsequently unavailable to human hunters in that region. Bien que le bison était le gros mammifère le plus abondant de la Béringie de l’Est pendant la plus grande partie des 100 000 dernières années, sa répartition a diminué considérablement à la fin du pléistocène et pendant l’holocène. Puisque la plupart des sites archéologiques présentent peu de restes d’animaux et que le contrôle chronologique des spécimens paléontologiques sur de grandes régions de la Béringie de l’Est laisse à désirer, cela rend difficiles les recherches portant sur la nature des interactions humaines avec le bison pendant la période de l’holocène. Nous avons examiné la ...